Platform of government services in citizen security - Silva Ruiz, Ronald (2011)
The purpose of this document is to define the scope of citizen security from the point of view of State intervention. In this sense, the concept of citizen security is broadened in order to analyze the causes that threaten it, configuring it in a situation of citizen insecurity. In this sense, based on a focus on the victim and the victimizer, the causes of citizen insecurity are sought, understanding this as a situation of danger or risk, or the occurrence of an event that violates some right. Thus, the analysis is distinguished by differentiating two moments, before the occurrence of an event that violates a right and after the occurrence of the event, for which State services aimed at prevention and others aimed at the care of victims and perpetrators emerge. Finally, the document seeks that the institutions identify their role within citizen security and emphasize, according to their competencies, the strengthening of the provision of citizen security services.